2021
DOI: 10.1111/eci.13549
|View full text |Cite
|
Sign up to set email alerts
|

Serum vaspin levels and carotid intima‐media thickness in predialysis patients

Abstract: Cardiovascular disease is the main cause of death among patients receiving chronic kidney disease (CKD) patients.Cardiovascular death is 10-20 times higher in such patients than in the general population. 1,2 Atherosclerosis begins many years before the development of clinical manifestations. 3,4 Carotid intima-media thickness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Elevated serum vaspin concentration is associated with obesity and altered insulin sensitivity in humans. As reported in previous studies, the serum vaspin level, if abnormally elevated, can induce abnormal lipid metabolism, and elevated levels of hormones in patients can lead to hormone regulation disorder and thus increase its content [ 36 ]. In animal experiments, Bongrani et al [ 37 ] found that when the body weight and insulin resistance index of obese diabetic rats rose, their serum vaspin levels also increased, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum vaspin concentration is associated with obesity and altered insulin sensitivity in humans. As reported in previous studies, the serum vaspin level, if abnormally elevated, can induce abnormal lipid metabolism, and elevated levels of hormones in patients can lead to hormone regulation disorder and thus increase its content [ 36 ]. In animal experiments, Bongrani et al [ 37 ] found that when the body weight and insulin resistance index of obese diabetic rats rose, their serum vaspin levels also increased, and vice versa.…”
Section: Discussionmentioning
confidence: 99%